THE EFFECTS OF AIRLINE HOSPITALITY ON THE ATTITUDE OF FULL-SERVICE AIRLINE PASSENGERS: A PRELIMINARY STUDY - Monizaihasra Mohamed; Zuraidah Zainol, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This study aims to identify the influence of perceived airline hospitality on passenger’s attitude. Data were gathered from a purposive sample of 200 full-service airline passengers using self-administered questionnaires. Regression analysis was used to test the hypotheses. The findings suggest that positive evaluation of airline hospitality has significant and positive influences on the passengers’ attitude towards the airline within the context of full-service airline. The outcome of this study provides airline service management with a new and useful insight on how to well manage the passenger’s in-flight experience and serves as a point of departure to the researchers in the field of hospitality and airline services.